DIAGNOSIS FILARIASIS BERDASAR HAPUSAN DARAH TEPI - H. I. Malewa; Prihatini . (Indonesian Association of Clinical Pathologist and Medical laboratory, 2008)
Filariasis is a disease group affecting humans and animals caused by nematode parasites of the order Filariidae, commonly calledfilariae. Filarial parasites may be classified according to the habitat of the adult worms in the vertebral host. the lymphatic groupincludes Wucheria bancrofti, Brugia malayi and Brugia timori. the cutaneous group includes Loa-loa, onchocerca volvulus, andMansonella streptocerca. the body cavity group includes Mansonella perstans and Mansonella ozzardi. these parasites are transmittedto humans through the bite of an infected mosquito. Clinical findings vary from asymptomatic until severe, depending on geography,parasite species, immune response and intensity of the infection A 19-years-old Javanese woman, presented with oedema on right legs.She has been suffering from oedema on right leg since she was 7-years-old. Physical examination showed elephantiasis on the right leg.Early, the patient had swelling in right inguinal area spreading into her right leg. the oedema was persistent and become larger untilnow. there was no fever and pain. She had history living in South Borneo when she was 1 until 4 years old. She did not receive anymedication before. Laboratory examination showed no abnormality both of complete blood count and clinical chemistry. From thin bloodsmear examination many forms of microfilariae were found. the data showed manifestation of filariasis in the blood.